A Problem of Enumeration of Two-color Bracelets with Several Variations - Shevelev, Vladimir (Journal of Informatics and Mathematical Sciences, 2011)
We consider the problem of enumeration of incongruent two-color bracelets of n beads, k of which are black, and study several natural variations of this problem. We also give recursion formulas for enumeration of t-color bracelets, t≥3.